Analysis Policy Digitalization of Education - Eldiana, Novia Frisda; Hadi, Syamsul; Sukma Indra Dewi , Radeni (Universitas Negeri Padang, 2025)
This study analyzes the gap between ambition and the implementation of policy digitalization in basic education in Indonesia. Aims to evaluate the effectiveness of equity and governance strategies, research. This uses the Systematic Literature Review (SLR) method with the PICOC framework against 17 articles from reputable journals and documents policy strategies for the 2019–2025 period. Study results reveal the existence of paradox technology: even though Indonesia has solid laws, such as the National Education System Law and Presidential Instruction No. 7 of 2025, as well as achievements in administrative tall in data integration through Dapodik and distribution devices, approach uniform implementation​ fails to accommodate disparity in infrastructure in the 3T region. This, in turn, widens the digital divide between areas. In addition, the high adoption of the Independent Teaching Platform (PMM) is seen as a success, more pseudo-driven by pressure, compliance, administrative and bureaucratic factors than by pedagogical motivation, which creates a cognitive burden for teachers. As solutions, research recommends reorienting governance through an infrastructure strategy, an asymmetric hybrid model, reinforcement of competence in digital leadership at the head of the school, and an adoption scheme financing cycle to life to ensure the sustainability of assets. In conclusion, the national digital transformation must quickly shift from merely modernizing administrative systems to implementing substantive changes to provide quality education.